2010
DOI: 10.1117/12.848233
|View full text |Cite
|
Sign up to set email alerts
|

An UGS radar with micro-Doppler capabilities for wide area persistent surveillance

Abstract: Detecting humans and distinguishing them from natural fauna is an important issue in security applications to reduce false alarm rates. In particular, it is important to detect and classify people who are walking in remote locations and transmit back detections over extended periods at a low cost and with minimal maintenance. The ability to discriminate men versus animals and vehicles at long range would give a distinct sensor advantage. The reduction in false positive detections due to animals would increase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 25 publications
(26 reference statements)
0
7
0
Order By: Relevance
“…Comparison with previous work [14] on horse and rider is given in Figure 6. The spectrogram in this case does not have range extent, and so the detection of the rider is not as easy.…”
Section: Comparison To Previous Workmentioning
confidence: 92%
See 1 more Smart Citation
“…Comparison with previous work [14] on horse and rider is given in Figure 6. The spectrogram in this case does not have range extent, and so the detection of the rider is not as easy.…”
Section: Comparison To Previous Workmentioning
confidence: 92%
“…Independent component analysis (ICA) can be used to extract independent basis functions from the spectrogram to be used as features in a classifier [13]. Micro-Doppler signatures have been suggested as a biometric [8], for distinguishing fauna from humans [14], and micro-Doppler features have been used in classification algorithms in [15,16,17]. Micro-Doppler signatures and direction-of-arrival (DOA) estimates have been extracted at over nine meters range through a brick wall [18].…”
Section: Introductionmentioning
confidence: 99%
“…In (Tahmoush et al, 2010), a 16 points scattering model of a 1.8m tall person walking at 1.5 m/s, as shown in Figure 4, is discussed. Figure 5 and Figure 6A show the movement of the corresponding simulated limbs and time-frequency spectrum, respectively.…”
Section: Scattering Model Based Feature Extractionmentioning
confidence: 99%
“…Micro-Doppler features have been used to differentiate targets among humans, animals and vehicles [ 79 ]. Researchers have found that it is possible to use micro-Doppler features to identify if the human subject is carrying a weapon [ 80 ].…”
Section: Emerging Applicationsmentioning
confidence: 99%